Mircea Popescu şi corespondenţii săi: Ştefan Baciu, N. P. Comnen, Neagu Djuvara, Mircea Eliade, Vintilă Horia, Virgil Ierunca, Petru Iroaie, Alexandrina Mititelu - Mihaela Albu (Revista de Istorie și Teorie Literară)
Mircea Popescu was a professor, literary critic and journalist who lived almost all his life in exile, in Italy, where he promoted the Romanian culture permanently. He has a very rich correspondence with Ștefan Baciu, N.P. Comnen, Neagu Djuvara, Mircea Eliade, Vintilă Horia, Virgil Ierunca, Petru Iroaie and Alexandrina Mititelu. Due to his daughter-in-law, Mrs. Simona Coleş-Popescu, we’ll include some unpublished letters sent by his friends and Romanian writers in a book dedicated to Mircea Popescu’s literary activity. In this article we publish two of them.